Factors Influencing Customer Loyalty Mediated by Customer Satisfaction on Imported Skincare in Batam City - Laurentcia Longli; Erilia Kesumahati (Universitas Batanghari Jambi, 2023)
Currently, world beauty Is growing in Indonesia, especially in self-care. Women and men are also starting to take care of themselves by using skincare. Skincare is very important to use for beauty and self-care. Skincare now can be used in all various circles of people. There are so many skincare brands from local and imports circulating in Indonesia, especially in Batam. However, many people prefer to use imported skincare products from South Korea. This study was conducted to know the effect of product quality, trust, brand image, promotion, and price on customer loyalty to import skincare products mediated by customer satisfaction in Batam City. The sample of this research is users of Korean skincare in Batam City with a total of 409 respondents through questionnaires distribution. The data were processed by using SmartPLS 3.2.9 software. The results of this research is that there is a significant positive effect of product quality, brand image, promotion, and price on customer loyalty. Meanwhile, trust does not have a significant positive impact on customer satisfaction and trust does not have a significant positive impact on customer loyalty mediated by customer satisfaction.